The Effect of Cooking Method and Cooked Color on Consumer Acceptability of Boneless Pork Chops - Lauren T. Honegger; Erin E. Bryan; Hannah E. Price; Taylor K. Ruth; Dustin D. Boler; Anna C. Dilger (Foods, 2021)
The objective was to determine the effects of sous-vide cooking and degree of doneness on consumer eating experience of pork chops when cooked color was expected to differ. The hypothesis was consumers would prefer a cooked brown color and would rate grilled chops more acceptable than sous-vide chops. Chops were cooked to 63 °C or 71 °C using either an open-hearth grill or a sous-vide device. Participants evaluated four samples for tenderness, juiciness, flavor, and overall acceptability. Participants rated a greater percentage of chops cooked sous-vide at 63 °C as tender (82.82%), juicy (55.83%) and acceptable (60.34%) compared with all other cooking method and degree of doneness combinations. Participants rated a greater percentage of sous-vide chops as tender and acceptable compared to grilled chops. Participants rated a greater percentage of chops cooked to 63 °C as tender, juicy, flavorful, and acceptable when compared to 71 °C. Even when participants could visualize cooked color, they preferred chops cooked to 63 °C compared with chops cooked to 71 °C. Overall, participants preferred chops cooked to 63 °C compared to 71 °C regardless of the cooking method and preferred chops cooked to 63 °C using the sous-vide cooking method the most among all treatments.